\(H\)-\(E\)-Super Magic Graceful Labelings of Graphs - Kumar, Duraisamy; Mohankumar, Elakkiya; Lawrance, J. Sebastian; Bhuvaneshwari, M. (Communications in Mathematics and Applications, 2025)
This article examines H-E-Super Magic Graceful Labelings (H-E-SMGL) of graphs. These labelings provide a systematic way to analyze how graphs can be decomposed into subgraphs with specific properties, particularly in the context of H-coverings. We investigate several families of graphs, including fans, books, and grids admits H-E-SMGL.